Analisis Aplikasi Sakti Terhadap Efektifitas Penyusunan Laporan Keuangan dengan Mediasi Komitmen Pimpinan - Tauristasari, Lila; Gideon Setyo Budiwitjaksono; Tantina Haryati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research to examine the influence of understanding accrual-based government accounting standards, utilization of the SAKTI application and competence on the effectiveness of preparing financial reports with leadership commitment as a mediation variable in the work unit of the Ministry of Education, Culture, Research and Technology. The population to be studied are Computer Recording Officers, namely SAKTI Application Operators and Accounting/Verification Officers, namely Commitment Making Officers who are involved in preparing financial reports at the Budget User Authorization Accounting Unit (UAKPA) level at the Working Unit of the Ministry of Education, Culture, Research and Technology with totaling 75 respondents. The data used in this research was analyzed using the Partial Least Square (PLS) approach with the help of the smart PLS 3.0 analysis tool. Based on the measurement results, it shows that Understanding Accrual-Based Government Accounting Standards has an influence on the Effectiveness of Preparing Reports, Utilization of the SAKTI Application has an influence on the Effectiveness of Preparing Financial Reports, Competence has an influence on the Effectiveness of Preparing Financial Reports, Understanding Accrual-Based Government Accounting Standards have an influence on the Effectiveness of Preparing Financial Reports through the Commitment of Employee Work Leaders, Utilization of the SAKTI Application has an influence on the Effectiveness of Financial Report Preparation through the Commitment of Employee Work Leaders, Competence has an influence on the Effectiveness of Financial Report Preparation through the Commitment of Employee Work Leaders.